2012
DOI: 10.1083/jcb.201203061
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant substrate engagement of the ER translocon triggers degradation by the Hrd1 ubiquitin ligase

Abstract: The Hrd1 ubiquitin ligase plays a role in quality control of two substrates associated with the Sec61 translocon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(113 citation statements)
references
References 70 publications
5
106
0
Order By: Relevance
“…Pulse-Chase Assays-Pulse-chase analysis was performed as described (13,16,20,35). Briefly, log phase yeast cultures grown in SD medium (plus 200 M CuSO 4 for pOC9-URA3-HA-CL1-transformed strains) were labeled with ϳ20 Ci of Tran 35 Slabel (MP Biomedicals, GE Healthcare) per A 600 unit of cells for 5-10 min in SD medium lacking methionine and cysteine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulse-Chase Assays-Pulse-chase analysis was performed as described (13,16,20,35). Briefly, log phase yeast cultures grown in SD medium (plus 200 M CuSO 4 for pOC9-URA3-HA-CL1-transformed strains) were labeled with ϳ20 Ci of Tran 35 Slabel (MP Biomedicals, GE Healthcare) per A 600 unit of cells for 5-10 min in SD medium lacking methionine and cysteine.…”
Section: Methodsmentioning
confidence: 99%
“…For all experiments, yeast was grown at 30°C. Standard methods were used for recombinant DNA manipulations (20).…”
Section: Methodsmentioning
confidence: 99%
“…2) (41,54). Importantly, deletion of RKR1 increased the abundance of the faster migrating (translationally paused) species of this protein (Vma12(glyc)-K12) (Fig.…”
Section: Rkr1 Regulates Abundance Of a Model Translationally Stalled mentioning
confidence: 99%
“…It has been reported that HRD1 and gp78 are two ERAD-related E3 ubiquitin ligases that are associated with the ER membrane (Chen et al, 2006;Kostova et al, 2007). Hrd1 forms a complex with SEL1L and mainly mediates the degradation of soluble, ER-luminal substrates and integral membrane proteins (Rubenstein et al, 2012;Shmueli et al, 2009). gp78, which was the first described and is the best documented human ERAD E3, is a multi-spanning membrane protein with its catalytic domain facing the cytosol (Chen et al, 2006;Fang et al, 2001;Li et al, 2009).…”
Section: E2-e3 (Ube2g2-gp78)-complex-mediated Herp Ubiquitylationmentioning
confidence: 99%